Extraction of high quality DNA from Cola nitida and Cola acuminata - Adesoye, A.I.; Fasola, T.R.; Akinro, L.A. (Research in Plant Biology, 2014)
Cola spp. are highly valued in African traditional medicine because they are rich in common and rare phytochemicals. They are important raw material in both the food and pharmaceutical industries. It is often difficult to isolate DNA from many tropical species with high polyphenolic and alkaloid contents. Many published protocols for nucleic acid isolation failed to yield sufficiently good quality amounts of DNA from leaf samples of C. nitida and C. acuminata for analysis. In this research, a simple and fast sodium dodecyl sulphate (SDS) – based extraction protocol have therefore been developed for routine isolation of high-quality nucleic acids from these Cola species by modifying established protocols. Genomic DNA obtained was found suitable for PCR amplifications.